2006
DOI: 10.1139/x05-236
|View full text |Cite
|
Sign up to set email alerts
|

Landscape-scale spatial patterns of winter injury to red spruce foliage in a year of heavy region-wide injury

Abstract: Red spruce (Picea rubens Sarg.) winter injury is caused by freezing damage that results in the abscission of the most recent foliar age-class. Injury was widespread and severe in the northeastern United States in 2003 and was assessed at multiple elevations at 23 sites in Vermont and adjacent states. This paper presents a spatial analysis of these injury assessments. Relationships between winter injury on dominant and codominant spruce trees and elevation, latitude, longitude, slope, and aspect were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Lazarus et al (2006) reported that conifers in the western part of our study region were more stressed than trees in the eastern part of the region. For red spruce, that stress is associated with reduced freezing tolerance and increased winter injury.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Lazarus et al (2006) reported that conifers in the western part of our study region were more stressed than trees in the eastern part of the region. For red spruce, that stress is associated with reduced freezing tolerance and increased winter injury.…”
Section: Discussionmentioning
confidence: 62%
“…These include soil and surface water acidification, plant nutrient imbalances which may ultimately result in declines in forest health and, over the long term, changes in species composition (Nihlgard, 1985;Aber et al, 1989;Schaberg et al, 2002). Trees at higher elevations are typically affected more than those at lower elevations, because of elevated N deposition and poor site quality (Johnson et al, 1992;Lazarus et al, 2006). Different tree species may exhibit varying levels of susceptibility to elevated N inputs; often coniferous species, which have lower biological N demand and are better adapted to poorer quality/ low nutrient sites are impacted more by increases in N availability (Southern Forest Resource Assessment;SOFRA, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…3), which was likely able to capture canopy space opened by mortality of red spruce and paper birch. The decline of the red spruce is likely related to increased winter injury from acidic deposition, which is more severe at higher elevations (33,34). Paper birch may also be adversely affected by increasing frequency of freeze-thaw events associated with climate change (35).…”
Section: Resultsmentioning
confidence: 99%
“…in the northeastern United States, both winter desiccation (Curry and Church 1952, Hadley et al 1991 and dehardening/freezing damage (Peart et al 1991;Perkins and Adams 1995;Strimbeck et al 1995;Lazarus et al 2004Lazarus et al , 2006 have been suggested as causal factors. In this paper we examine the possible causes of widespread conifer damage in northern Ontario and identify next steps to improve our understanding of this recurring phenomenon.…”
Section: Ricardo Velasquezmentioning
confidence: 99%
“…Some researchers believe that the damage is associated with fluctuations of warm and freezing temperatures in winter months (Henson 1952, Cayford et al 1959, Robin and Susut 1974. In the well-studied syndrome of red spruce winter injury in the northeastern United States, both winter desiccation (Curry and Church 1952, Hadley et al 1991 and dehardening/freezing damage (Peart et al 1991;Perkins and Adams 1995;Strimbeck et al 1995;Lazarus et al 2004Lazarus et al , 2006 have been suggested as causal factors. In this paper we examine the possible causes of widespread conifer damage in northern Ontario and identify next steps to improve our understanding of this recurring phenomenon.…”
mentioning
confidence: 99%